2022
DOI: 10.3389/fneur.2021.811518
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Immunosenescene and Inflammaging: Relevance to the Immunopathogenesis and Treatment of Multiple Sclerosis

Abstract: Aging is characterized, amongst other features, by a complex process of cellular senescence involving both innate and adaptive immunity, called immunosenescence and associated to inflammaging, a low-grade chronic inflammation. Both processes fuel each other and partially explain increasing incidence of cancers, infections, age-related autoimmunity, and vascular disease as well as a reduced response to vaccination. Multiple sclerosis (MS) is a lifelong disease, for which considerable progress in disease-modifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 447 publications
(484 reference statements)
0
17
0
Order By: Relevance
“…Up to 75% of patients with ON convert to full-blown MS between 10 years and 15 years after clinical onset [ 4 ]. Although disease causes have not completely been identified, the underlying mechanism is suggested to likely involve infiltration of inflammatory cells (e.g., CD4 + T cells (known as T helper 17 cells) and CD8+ T cells) into and demyelination of optic nerve, axonal damage, and death of retinal ganglion cells (RGCs) [ 5 ], the projection neurons that convey visual signals from other retinal neurons to the brain. This neurodegenerative process leads to irreversible loss of vision.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 75% of patients with ON convert to full-blown MS between 10 years and 15 years after clinical onset [ 4 ]. Although disease causes have not completely been identified, the underlying mechanism is suggested to likely involve infiltration of inflammatory cells (e.g., CD4 + T cells (known as T helper 17 cells) and CD8+ T cells) into and demyelination of optic nerve, axonal damage, and death of retinal ganglion cells (RGCs) [ 5 ], the projection neurons that convey visual signals from other retinal neurons to the brain. This neurodegenerative process leads to irreversible loss of vision.…”
Section: Introductionmentioning
confidence: 99%
“…Patients over the age of 55 are usually excluded from clinical trials. Therefore, the safety and efficacy of DMTs in this group of patients is not confirmed [49]. Schweitzer et al [17] suggested that the benefits of high efficacy DMTs could decrease with age.…”
Section: Multiple Sclerosismentioning
confidence: 92%
“…One possible explanation is the impact of immunosenescence which is associated with the accumulation of unusual immune cell subsets that may play a role in the development of an early ageing process in autoimmunity [48]. Some features of immunosenescence found in aged healthy controls have already been observed in MS patients at a younger age [49].…”
Section: Multiple Sclerosismentioning
confidence: 99%
See 2 more Smart Citations